KAJIAN SIFAT FISIKA DAN KIMIA TANAH ULTISOL PADA LAHAN KELAPA SAWIT TAHUN TANAM 2000 DENGAN BEBERAPA JENIS VEGETASI YANG TUMBUH DI KEBUN PTP. NUSANTARA II TANJUNG GARBUS (Study of Physical and Chemical Soil Characteritics in Oil Palm Plantation on Plant Y - Zulhajji Zulhajji; Sumono Sumono; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2019)
ABSTRACT   Physical and chemical soil characteritics are important factors for the growth of oil palm. This research was aimed to study physical and chemical soil characteritics of the oil palm with vegetations of Pueraria javanica, grass, and no vegetation in Pagar Merbau PTP Nusantara II. The observed parameters were soil texture, porosity, water content of field capasity, soil permeability, total Nitrogen, available Phospate, and land Potassium exchange. The results showed that the soil type was ultisol, with sandy loam texture and pH of 5,17-5,31 (acid). The vegetation soil had porosity of 39-40 % at a depth of 5 cm and 37-38 % at a depth of 25 cm. The water content of field capacity was ranged from 21,9-26,4 % at a depth of 5 cm and 21,1-25,5 % at a depth of 25 cm. Permeability was ranged from 3,01-6,83 cm/h. Total N was 0,05-0,10 %. P available was ranged from 7,45-10,48 ppm. K exchange of land was ranged from 0,10-0,75 me/100g. The soil with no vegetation had porosity of 39 % at a depth of 5 cm and 38 % at a depth of 25 cm. The water content of field capacity was 21,9 % at a depth of 5 cm and 21,4 % at a depth of 25 cm. Permeability was 3,01 cm/h. Total N was 0,05 %. P available was 7,47 ppm. K exchange of land was 0,75 me/100g. Keywords: Soil Physical And Chemical, Vegetation, Oil Palm Plantation, Ultisol ABSTRAK   Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan kelapa sawit. Penelitian ini bertujuan untuk mengkaji sifat fisika dan kimia tanah ultisol pada lahan kelapa sawit dengan vegetasi kacang-kacangan (Pueraria javanica), rumput dan tanpa vegetasi di Kebun PTP. Nusantara II Pagar Merbau. Parameter yang diamati meliputi tekstur tanah, porositas, kadar air kapasitas lapang, permeabialitas tanah, N-total, P tersedia dan K tukar tanah. Hasil penelitian menunjukkan jenis tanah di daerah penelitian adalah ultisol bertekstur lempung berpasir dan pH 5,17-5,31 (masam). Tanah dengan vegetasi mempunyai porositas berkisar 39-40 % pada kedalaman 5 cm dan 37-38 % pada kedalaman 25 cm, kadar air kapasitas lapang 21,9-26,4 % pada kedalaman 5 cm dan 21,1-25,5 pada kedalaman 25 cm, permebilitas berkisar 3,01-6,83 cm/jam, N-total 0,05-0,10 %, P tersedia 7,45-10,48 ppm, K tukar tanah 0,10-0,75 me/100g. Tanah tanpa vegetasi mempunyai porositas berkisar 39 % pada kedalaman 5 cm dan 38 % pada kedalaman 25 cm, kadar air kapasitas lapang 21,9 % pada kedalaman 5 cm dan 21,4 % pada kedalaman 25 cm, permebialitas berkisar 3,01 cm/jam, N-total 0,05 %, P tersedia 7,47 ppm, K tukar tanah 0,75 me/100g. Kata Kunci: Fisika dan kimia tanah, vegetasi, kebun kelapa sawit, ultisol